Strategic Alliances and Financial Performance: Some Empirical Evidence of Bio-Pharmaceutical Industry: Strategic Alliances and Financial Performance - Chakir lamrani, Houda (International Journal of Scientific Research and Management (IJSRM), 2019)
Over the last decades, strategic alliance have played an important role among high tech firms, including biotech and pharmaceutical companies, showing an impact on financial performance. This study focuses on this topic and analyses how strategic alliances portfolios and types of the partnerships affect bio-pharmaceutical companies’ financial performances. Drawing upon a panel data set of 158 alliances during the period of 2003-2013, empirical findings highlight that the number of alliances has a negative relationship with financial performance, whereas partnership types such as licensing and co-development have a positive relationship with the financial performance of biotech and pharmaceutical companies.